A Pragmatic Analysis of Audioslave's Rock Lyrics: Conversational Implicature and Flouted Maxims - Petrina; Afriana (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates how conversational implicature and the flouting of Grice’s cooperative maxims are embedded in the lyrics of the American rock band Audioslave. Drawing on pragmatic theory, the research aims to identify how implicit meanings are constructed through non-literal expressions in song lyrics. A qualitative descriptive method was applied to twenty-five lyric lines selected from five songs which are Like a Stone, I Am the Highway, Show Me How to Live, Shadow on the Sun, and Be Yourself. The analysis shows that the Maxim of Quality is most frequently flouted, followed by the Maxims of Manner, Quantity, and Relation. These floutings manifest through metaphor, ambiguity, and symbolic imagery that require listeners to interpret meanings inferentially. Interpreting maxim violations in lyrics demonstrates that even non-dialogic texts operate according to pragmatic principles, revealing how musicians strategically use figurative language to communicate emotional, existential, and philosophical themes. By applying Gricean theory to musical discourse, this study expands the scope of pragmatics beyond spoken interaction and demonstrates how song lyrics function as intentional communicative acts that convey layered meaning through implicature. The findings contribute to a deeper understanding of how listeners derive interpretation from artistic language and highlight the value of pragmatic analysis in music studies.